Kecerdasan Emosional dan Prestasi Belajar Siswa Kelas XI Sma di Bondowoso - Muchammad Priyangga; Zulaikhah, Siti (Sintesis: Jurnal Bimbingan Konseling, 2023)
This study aims to determine the relationship between emotional intelligence and student achievement in class XI at SMA Negeri 1 Bondowoso in the 2020/2021 academic year. This study used 32 students as subjects. The data collection method in this study used the Likert Scale method, while the instrument used was the Emotional Intelligence questionnaire with 50 items. From the results of these calculations, the results of the correlation coefficient r = -0.535 are obtained. In accordance with the provisions of the moment product formula, that the value of r ranges from -1 to +1 (-1 = r = +1), where if the price of r = -1 then there is a negative correlation which states that there is a strong relationship between emotional intelligence and learning achievement. Keywords: emotional intelligence, learning achievement